Ramón Gaya - María Zambrano: Elective Affinities - Chacón, Pedro (Escritura e Imagen, 2012)
As well as the biographical coincidences between Ramón Gaya and María Zambrano during the Civil War and the long exile that followed, it is worth mentioning the profound harmony and multiple parallels that exist between the work of both authors. the present study analyses the existential roots of these affinities between the painter and the philosopher, and also the deep convergence of their positions about art and creative work. this convergence is based on a similar conception of the “real” as “sacred”. the study also tries to show the limits of this convergence as exemplified by the different approach of their analysis of the “symbolic truth” and the “pictorial truth” in Velázquez’s work “El niño de Vallecas” ( the Boy from Vallecas).